Closing a Failed Bank : Resolution Practices and Procedures - Parker, David (International Monetary Fund, 2011)
This manual addresses problem bank resolution from the time a bank is identified as being in financial trouble through intervention to liquidation. It comes with an interactive CD-Rom from which users can download and tailor documents to use in their own closing processes. The book draws on the author's lengthy career as a bank liquidator for the Federal Deposit Insurance Corporation and Resolution Trust Corporation and his worldwide consulting experience with the IMF and other international organizations.